Ocular complications of heart, lung, and liver transplantation. Issue 4 (1st April 1998) - Ng, Paul; McCluskey, Peter; McCaughan, Geoff; Glanville, Allan; MacDonald, Peter; Keogh, Anne
Abstract : AIM: To document the nature and frequency of ocular complications in a large group of patients who underwent heart, lung, or liver transplantation. METHODS: A retrospective audit of the medical records of all patients undergoing heart, lung, or combined heart-lung transplantation at St Vincent's Hospital, Sydney, or liver transplantation at Royal Prince Alfred Hospital Sydney, was performed to detect patients with symptomatic ocular complications following transplantation. 19 of 860 patients were identified as having ocular complications. RESULTS: Ocular complications occurred in 2% of patients with 65% of these being opportunistic infections. Herpes group viral retinitis (77%) and fungal chorioretinitis (22%) were seen. Other complications included choroidal pseudolymphoma, central retinal vein occlusion, herpes zoster ophthalmicus, herpetic keratitis, dacryocystitis, cyclosporin retinopathy, and rifabutin associated uveitis. CONCLUSION: Herpes group viral retinitis was the most common ocular opportunistic infection and occurred most frequently during the second year after transplantation. Delayed diagnosis was associated with poor visual outcome.